Automatic modelling of complex geometries for MCNP simulation using GEOMIT code. (2015) - Shaaban, Noha; Gammal, Wael El; Nasif, Hesham; Morota, Hidetsugu
The need for an automatic CAD/MCNP conversion interface appeared due to the complexity of the geometries and the difficulty to transfer their models to the MCNP input manually. GEOMIT is a code that has been developed to automatically generate MCNP surface and cell cards with the capability to produce solid and void cells in a simple geometry without using union or complement operators. This work shows the success of the code for modelling different test cases for the active well coincidence counter geometry which is of great importance for nuclear safeguard applications. Also, a great improvement in calculation time was obtained compared to the manual geometry calculations due to explicit void creation.